FUNGSI KOMUNIKASI KELUARGA BERDAMPAK PADA PERKEMBANGAN KEDISIPLINAN ANAK - Agussalim Waangsir (JSSHA ADPERTISI JOURNAL, 2022)
Require to be done in family in that is fertilize the attitude of child discipline are family member can conduct the communications better and correctness which is adapted for by a time, place, atmosphere, age so that earn constructive of harmonious relation in family. This research design uses a qualitative approach. The research technique used in this research is literature study, namely by researching and understanding books, documents or other relevant written sources. Process the communications represent system of where the communications process can only take place maximal if provided with the communications elements. Relation and comminications among father, mother, child and also other; dissimilar family member very need in everyday life because can foster the personality and also improve the attitude of child discipline. No relation or kesenjangan relation among family member at home can make the child feel the disrespect, do not discipline, and lazy learn the.